Chemistry and Transport of Potassium during the Non‐Steady State of Syenite Leaching. Issue 1 (16th February 2017) - Li, Kejing; Dawydiak, Christi A.
Abstract : Core Ideas: A flow system for the release and extraction kinetics of ions from a rock fertilizer. The initial release of ions from syenite studied using ICP‐MS and a pH meter. Fast surface potassium–proton ion exchange and K desorption observed. Syenite is mainly composed of potassium feldspar (Kfs), which is a structural K‐bearing mineral in soil, typically considered as an insoluble K resource. In contrast to the slow dissolution process, the initial non‐steady state stage usually gives a fast K + release rate and quickly decreasing, which is closely related with surface reactions. This process in a flow reactor has not been fully understood with a kinetic model. Earlier research about albite found that ion exchange and surface cation desorption occur rapidly, which leads to experimental efforts of this work. The 140‐mesh (105‐μm) and 325‐mesh (44‐μm) syenite leaching tests were performed under room temperature and pressure, using pH 1 and 3 diluted nitric acids, and flow rates from 0.01 to 1 mL min −1 in a packed‐bed flow reactor. Inductively coupled plasma mass spectrometry was used to measure the ions' (K +, Na +, Al 3+, Si 4+, Ca 2+, Fe 3+, Ba 2+ ) time‐dependent concentrations simultaneously. The pH measurement was added to monitor the consumption of reactant H +, providing reactant information crucial for understanding the surface reactions. The two fast surface reactions previously observed with albite were also observed with Kfs during the non‐steady state. The initial K + release kinetics were different from H + adsorption and other surface atoms detachment. The slow dissolution reaction and the influence of transport factors were also evaluated. A model has been built with two parts that include the fast reactions and the transport‐dissolution terms, conforming to the first‐order equation with a leachant pH correction factor and a parabolic diffusion equation.